The science of managing our digital stuff - Bergman, Ofer; Whittaker, Steve, 1957- (MIT Press, 2016)
Why we organize our personal digital data the way we do and how design of new PIM systems can help us manage our information more efficiently.- Resumé vydavatel
Keywords: informační management; organizace informací; vyhledávání informací; zpracování informací; informační věda; information management; information organization; information retrieval; information processing; information science; elektronické knihy; příručky; electronic books; handbooks and manuals